Food fight: From plunder and profit to people and planet - Gillespie, Stuart (HarperCollins, 2025)
Food is life, but our food system is killing us. Designed in a different century for a different purpose—to mass-produce cheap calories to prevent famine—it’s now generating obesity and ill-health and driving the climate crisis. We need to transform it into one that can nourish all eight billion of us and the planet we live on.